A Longitudinal Study to Better Understand Child Protection Intervention for First Nations Children - De La Sablonnière-Griffin, Mireille; Collin-Vézina, Delphine; Esposito, Tonino; Dion, Jacinthe (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2023)
This study brings forward new evidence regarding child protection (CP) intervention for First Nations children and contributes to a longitudinal understanding of their trajectories within CP services. It raises questions regarding the persisting, unmet needs of First Nations children, families, and communities by identifying the CP factors associated with a first decision to provide post-investigation intervention and a first decision to close a case following post-investigation intervention among First Nations children. Anonymized administrative data (2002–2014; n = 1340) were used to conduct multivariate analyses, including longitudinal analyses using Cox proportional hazards modeling. Among First Nations children, those who were very young, who were reported for serious risk of neglect, and whose situation included indicators of repeated individual or family contact with CP services were more likely to receive post-investigation intervention. Similarly, those who were very young, provided services for neglect or serious risk of neglect, and whose situation was investigated at least twice before intervention was provided were more likely to have a longer first episode of intervention. The longitudinal analyses also revealed that more than one in two First Nations children (51.7%) receiving post-investigation intervention experienced a placement in out-of-home care during their interaction with CP services. This study contributes to a better understanding of intervention for First Nations children in Canada. It highlights how First Nations children receiving CP intervention live in situations in which their needs persist over time and how current services do not appear able to respond to these situations adequately, supporting the move towards autonomous, Indigenous–led CP services.